SUSTAINABLE BEEF CATTLE DEVELOPMENT BASED ON REGIONAL POTENTIAL IN MUSI RAWAS REGENCY - Bagus Dimas Setiawan; Zulhapi Utama Adlan; Judo Laksono (Universitas Muhammadiyah Malang, 2026)
This study aimed to analyze the potential for sustainable beef cattle development based on regional potential in Musi Rawas Regency. The research employed a descriptive-analytical quantitative method using the approaches of Location Quotient (LQ), land carrying capacity analysis, capacity for increasing ruminant livestock population (KPPTR), and Logical Framework Approach (LFA). The data used in this study were secondary data obtained from relevant institutions. The results showed that several districts in Musi Rawas Regency were classified as base areas for beef cattle development with LQ values > 1, namely Megang Sakti, Tugumulyo, STL Ulu Terawas, Muara Beliti, and Sumberharta Districts. The potential production of forage feed and agricultural waste in Musi Rawas Regency reached 3,378,148 tons of dry matter/year with a livestock population increase capacity of 1,468,760 animal units (AU). Megang Sakti District had the highest development capacity of 309,061 AU, making it the most potential area for beef cattle development. Sustainable beef cattle development can be achieved through optimizing local resource utilization, strengthening farmer institutions, improving human resource quality, integrating crop and livestock farming systems, and enhancing livestock marketing systems. Based on the research findings, Musi Rawas Regency has significant potential for sustainable beef cattle development based on regional potential.